A New Perspective from Time Use Research on the Effects of Lockdown on COVID-19 Behavioral Infection Risk - Jonathan I. Gershuny; Oriel Sullivan; Almudena Sevilla; Marga Vega-Rapun; Francesca Foliano; Juana Lamote de Grignon; Teresa Harms; Pierre Walthery (Institute of Labor Economics (IZA), 2020)
We present findings from the first two waves of an innovative, population-representative, UK time-use diary survey conducted both pre- and mid-lockdown, using an online diary instrument that proved both reliable and quick-to-field. Combining diary information on activity, location, and co-presence to estimate infection risks associated with daily behavior, we show clear changes in such behavior related to infection risk between the pre- and mid-lockdown periods: a substantial reduction of time spent in those behaviors with the highest levels of risk, accompanied by an equivalent increase in low-risk behavior. Because, in general, a populations' time use changes relatively slowly, the behavioral changes revealed may be interpreted directly as a consequence of the UK COVID-19 'lockdown' regulations. Subsequent waves will reveal the behavioral consequences of future changes in regulation.
Keywords: J10; I10; 330; behavioural risk; infection; COVID-19; time-use